Terjebak dalam Kemacetan: Eksplorasi Subjective Well-Being Pekerja Komuter Jakarta - Loveita, Lola; Nata Raditya, Dewa Gede; B. Arafah, Fajriah Rahmah; Indah Sari, Riska; Halida, Rizka (Personifikasi: Jurnal Ilmu Psikologi, 2025)
Commuting is a daily reality for many workers in the Jakarta area and its surroundings. Previous studies have established that commuting exerts a significant influence on individual subjective well-being (SWB). This research aims to investigate the various factors that shape the relationship between commuting experiences and the subjective well-being of workers in Jakarta and neighboring regions.  Employing a qualitative phenomenological approach, the study utilizes thematic analysis to uncover pivotal themes affecting the SWB of commuter workers. Data was gathered through in-depth interviews with six participants, aged 23 to 51, residing in the Jakarta vicinity. The findings indicate that commuting experiences have a notable impact on the SWB of these workers, with negative emotions often predominating, despite some positive sentiments reported. Job satisfaction emerges as a crucial factor in understanding commuting dynamics; however, this satisfaction can sometimes come at the expense of well-being in other aspects of life. Workers with families encounter heightened challenges in achieving a balance between subjective well-being and the competing demands of work and family responsibilities. Coping strategies adopted by individuals are vital for enhancing subjective well-being, particularly in light of technological advancements. Furthermore, finding ways to engage in meaningful leisure activities plays an essential role in boosting SWB. External factors, including transportation policies and work arrangements, are also recognized as influential in improving individual subjective well-being